2022
DOI: 10.1002/admt.202101282
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating the Perovskite Solar Cell Manufacturing Bottleneck via High‐Speed Flexography

Abstract: Perovskite solar cells have potential to deliver terawatt‐scale power via low‐cost manufacturing. However, scaling is limited by slow, high‐temperature annealing of the inorganic transport layers and the lack of reliable, large‐area methods for depositing thin (<30 nm) charge transport layers (CTLs). We present a method for scaling ultrathin NiOx hole transport layers (HTLs) by pairing high‐speed (60 m min−1) flexographic printing with rapidly annealed sol–gel inks to achieve the fastest reported process for f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Huddy et al developed ultrathin NiO x HTL by combining high-speed (60 m min -1 ) flexographic printing and the fastest annealing of the printed ink to fabricate PSCs. [179] Also, they engineered the viscosity of the ink by varying the ratio of the solvents (2-methoxy ethanol to ethanol) and concentration of the solute to achieve printed NiO x films with a thickness of 5-20 nm over a large area of 140 cm 2 (Figure 6b) and high uniformity (Figure 6c). In contrast, the thickness of the spin-coated film was 30 nm.…”
Section: Flexographic Printingmentioning
confidence: 99%
“…Huddy et al developed ultrathin NiO x HTL by combining high-speed (60 m min -1 ) flexographic printing and the fastest annealing of the printed ink to fabricate PSCs. [179] Also, they engineered the viscosity of the ink by varying the ratio of the solvents (2-methoxy ethanol to ethanol) and concentration of the solute to achieve printed NiO x films with a thickness of 5-20 nm over a large area of 140 cm 2 (Figure 6b) and high uniformity (Figure 6c). In contrast, the thickness of the spin-coated film was 30 nm.…”
Section: Flexographic Printingmentioning
confidence: 99%
“…Flexography provides a method for additive patterning, or patterning during deposition, as shown in Figure a, eliminating the need for additional laser scribing steps required during perovskite device fabrication and facilitating controlled crystallization through integration with an inline drying process. We have previously shown that this flexographic process can be used to print high‐quality charge transport layers such as NiO x , [ 34 ] affording the potential for integrating multiple flexography steps in series to achieve a fully scalable PSC fabrication process. Flexography uses an anilox roller with controllable cell depths in combination with a steel doctor blade to meter the volume of ink on the roller before it is transferred to a photopolymer stamp with raised pattern features and then printed on the substrate, as shown in our setup in Figure 1b.…”
Section: Resultsmentioning
confidence: 99%
“…Precise rheological design of the perovskite precursor and control over the physics of the printing process allow for targeting an optimal absorber thickness. [ 34 ] For flexographic printing, the anilox roller's cell depth and cell density control the metered ink volume, which, in combination with the ink transfer ratio, fully determine the thickness of a deposited wet film.…”
Section: Resultsmentioning
confidence: 99%
“…[17] Especially, the materials and operation processes are key factors in fabricating high-quality perovskite film with exceptional light absorbing and carrier transport abilities. [18] In the literature, many processes have been developed to prepare perovskite films, [19][20][21][22][23][24][25] in aiming to control the nucleation and growth of the films, thereby, obtaining film with dense microstructure and little voids. The most common method utilized is the solution process carried out under low-temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, many processes have been developed to prepare perovskite films, [ 19–25 ] in aiming to control the nucleation and growth of the films, thereby, obtaining film with dense microstructure and little voids. The most common method utilized is the solution process carried out under low‐temperature conditions.…”
Section: Introductionmentioning
confidence: 99%